Cleidocranial Dysplasia: Report of Two Cases - Avinash Kshar; H R Umarji (Wolters Kluwer Medknow Publications, 2010)
Cleidocranial dysplasia constitutes a congenital disorder manifested primarily in the development of facial and cranial bones, as well as partial development or complete absence of the clavicles and problems also arise on the number and eruption of teeth. It is a rare disease with autosomal dominant but 40% cases represented spontaneous mutations. This disease has no sex predilection. It is characterized by a generalized skeletal dysplasia. 1 In this article we are reporting two cases of cleidocranial dysplasia in son and father with characteristic clinical and radiographic features.